2019
DOI: 10.3390/w11071398
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change and Land-Use Change on Hydrological Extremes in the Jinsha River Basin

Abstract: Hydrological extremes are closely related to extreme hydrological events, which have been and continue to be one of the most important natural hazards causing great damage to lives and properties. As two of the main factors affecting the hydrological cycle, land-use change and climate change have attracted the attention of many researchers in recent years. However, there are few studies that comprehensively consider the impacts of land-use change and climate change on hydrological extremes, and few researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 72 publications
2
27
0
2
Order By: Relevance
“…Several studies have reported that surface runoff is more sensitive to land cover change than to climate change [4,34,71]. In contrary, there are studies that have argued that surface runoff is more sensitive to climate change than to the land cover change [22,72]. Similarly, a study of small watershed located in the upper Blue Nile basin showed that AET is more sensitive to land cover change than to climate change [71].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that surface runoff is more sensitive to land cover change than to climate change [4,34,71]. In contrary, there are studies that have argued that surface runoff is more sensitive to climate change than to the land cover change [22,72]. Similarly, a study of small watershed located in the upper Blue Nile basin showed that AET is more sensitive to land cover change than to climate change [71].…”
Section: Discussionmentioning
confidence: 99%
“…Human-induced land cover change is reported to have an impact on the regional climate [48]; however, Yin et al [49] pointed out that for the whole JRB, the share of each primary land use category did not vary notably from 1975 to 2000. Additionally, from 1970 to 2017, land use change exerted little impact on runoff extremes, while climate change was one of the main factors that led to changes in extreme hydrological situations [50]. did not vary notably from 1975 to 2000.…”
Section: Study Area and Observation Datamentioning
confidence: 94%
“…did not vary notably from 1975 to 2000. Additionally, from 1970 to 2017, land use change exerted little impact on runoff extremes, while climate change was one of the main factors that led to changes in extreme hydrological situations [50]. Annual air temperature and precipitation in the JRB have a high spatial variability, where the southeastern JRB is warmer and wetter than the northwestern area (Figure 2a,c,e).…”
Section: Study Area and Observation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Many research topics regarding the rainfall-runoff model have been studied, developed, and applied by hydrologists and irrigation engineers for many aspects. For example, Chen, et al [6], Kabiri, et al [7], Lin, et al [8] applied the rainfall-runoff model to assess runoff impacts due to climate and land-use change. Kwak,et al [ 9] also used the rainfall-runoff model to reconstruct the missing runoff time-series information.…”
Section: Introductionmentioning
confidence: 99%